2019
DOI: 10.1038/s42005-019-0190-0
|View full text |Cite
|
Sign up to set email alerts
|

Light emission from the layered metal 2H-TaSe2 and its potential applications

Abstract: Conventional metals, in general, do not exhibit strong photoluminescence. 2H-TaSe 2 is a layered transition metal dichalcogenide that possesses metallic property with charge density wave characteristics. Here we show that 2H-TaSe 2 exhibits a surprisingly strong optical absorption and photoluminescence resulting from inter-band transitions. We use this perfect combination of electrical and optical properties in several optoelectronic applications. We show a sevenfold enhancement in the photoluminescence intens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…For example, it has been recently shown that 2H-TaSe 2 , while showing excellent conductivity properties, also exhibits strong photoluminescence and long photo-carrier lifetime, allowing active metal-based device applications. 8 CDW is a macroscopic state which is exhibited by materials with reduced dimension, for example, one-dimensional and layered two-dimensional crystals. It is a result of modulation in the electronic charge arising due to a periodic modulation in the crystal lattice.…”
mentioning
confidence: 99%
“…For example, it has been recently shown that 2H-TaSe 2 , while showing excellent conductivity properties, also exhibits strong photoluminescence and long photo-carrier lifetime, allowing active metal-based device applications. 8 CDW is a macroscopic state which is exhibited by materials with reduced dimension, for example, one-dimensional and layered two-dimensional crystals. It is a result of modulation in the electronic charge arising due to a periodic modulation in the crystal lattice.…”
mentioning
confidence: 99%
“…2H-TaSe 2 , which exhibits charge density wave characteristics, is metallic at room temperature with a large work function of ∼5.5 eV . TaSe 2 serves as a passive semi-transparent electrode at the top, and it can also be replaced by other transparent electrodes like ITO or graphene. Figure c,d depicts the band bending in MoS 2 under equilibrium inferred from the sign of the short circuit current ( I sc ) and open-circuit voltage ( V oc ) across the junction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The material of focus in this work is 2H-TaSe 2 , which exhibits an incommensurate (IC-) CDW phase between 122 and 90 K, as well as a commensurate CDW phase below 90 K. [31,32] This material was chosen because it has already been used in the development of Hall devices, optoelectronics, and similar applications. [33][34][35][36] Additionally, since the superconducting phase transition of 2H-TaSe 2 occurs at 0.2 K, the corresponding phase does not coexist with CDW phase, making it easier to interpret calculations and experimental data. To date, CDW formation in 1L and few-layer 2H-TaSe 2 still remains a subject of debate, warranting an elaborate investigation like the one presented here.…”
Section: Doi: 101002/adts202100329mentioning
confidence: 99%